Detection of active human papilloma virus‐16 in head and neck cancers of Asian North Indian patients. (4th December 2015) - Sannigrahi, MK; Singh, V; Sharma, R; Panda, NK; Radotra, BD; Khullar, M
Abstract : Background: Head and neck cancers (HNC) are one of the most common cancers in India. Human papillomavirus (HPV) has been identified as an emerging risk factor for HNC. Methods: The present study was carried out to determine the active form of HPV‐16 using a combination of PCR, viral load determination, HPV‐16 E7 mRNA expression, p16, p53, and pRB immuno‐histochemistry (IHC). Results: A total of 226 HNC patients were enrolled in the present study. Sixty‐seven (29.7%) of HNC cases were found to be HPV DNA positive. Thirty‐two (14%) cases were HPV‐16 DNA positive and 20 (9%) cases expressed HPV‐16 E7 mRNA. HPV‐16 mRNA/p16 positive cases had significantly increased viral load and integrated HPV‐16 DNA. In summary, of total HNC patients, 6% cases were positive for both HPV‐16 DNA and p16, and 5% were positive for both E7 mRNA and p16 IHC. We observed similar HPV‐16 DNA/E7mRNA prevalence in oropharynx and oral cavity sites, however, oropharynx SCC had significantly higher viral load. Conclusion: Our results show low prevalence of active HPV‐16 in North Indian HNC patients. HPV‐16 E7 mRNA expression correlated with p16 nuclear positivity and increased viral load. Therefore, E7 mRNA expression may be used as a good surrogate indicator for active form of HPV‐16 infection.